Optical properties and oxidation of α-phase Ag–Al thin films. (26th January 2017) - De Silva, Kaludewa S B; Keast, Vicki J; Gentle, Angus; Cortie, Michael B
Abstract: We investigate a series of Ag–Al thin films containing up to 12 at% Al with the purpose of discovering whether these alloys would be a better choice for nanophotonic applications than pure Ag. Variable angle spectroscopic ellipsometry, AFM, x-ray diffraction and density functional theory are applied to explore and characterize the materials. Electromagnetic simulations of optical properties are used to place the results into a theoretical framework. We find that the increase in electron-to-atom ratio associated with the Al additions changes the optical properties: additions of the order of 1–2 at% Al are beneficial as they are associated with favorable changes in the dielectric function, but for greater additions of Al there is a flattening of the absorption edge and an increase in optical loss. In addition, contents of more than about 2 at% Al are associated with the onset of time-dependent intergranular oxidation, which causes a pronounced dip in the reflectance spectrum at about 2.3–2.4 eV (∼500–540 nm).